Preparation method of ultrafiltration membrane and ultrafiltration membrane
By using the interaction of polyether sulfone and sulfonated polysulfone with pore-generating agent, the preparation process of ultrafiltration membrane is simplified, and the ultrafiltration membrane with MWCO 5000 separation performance is achieved, solving the problem of cumbersome processes in the prior art. , improves separation performance and stability.
Patent Information
- Application Number
- CN202411526573.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the preparation method of MWCO 5000 ultrafiltration membranes is complicated, and there is a lack of a method for directly preparing ultrafiltration membranes that achieve MWCO 5000 separation performance through phase conversion method.
Vacuum defoaming treatment is performed using a precursor solution including organic solvents, polyether sulfones, sulfonated polysulfones and pore-generating agents, followed by gel bath treatment on the carrier to obtain high heat resistance, chemical stability and anti-oxidation properties. and mechanically strong ultrafiltration membranes, the separation performance of MWCO 5000 is achieved in one step through the interaction of sulfonated polysulfone and pore-generating agent.
The preparation process of ultrafiltration membranes is simplified, the material cost is reduced, the separation performance and stability is improved, the manufacturing time and cost are significantly reduced, and the problem of cumbersome process is solved.
Smart Images

Figure BDA0005109378120000081 
Figure BDA0005109378120000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ultrafiltration membranes, and in particular to a preparation method of an ultrafiltration membrane and an ultrafiltration membrane. Background Art
[0002] Molecular Weight Cut-Off (MWCO) 5000 means that the membrane can retain molecules with a relative molecular weight greater than 5000. MWCO5000 ultrafiltration membranes can effectively retain small molecular weight substances, improve separation purity and efficiency, meet the needs of high-precision separation, and have broad application prospects in many fields. For example, in the field of biopharmaceuticals, MWCO 5000 ultrafiltration membranes can be used for protein concentration and purification; in the food and beverage industry, MWCO 5000 ultrafiltration membranes can be used to remove impurities and concentrate nutrients; in environmental protection, MWCO 5000 ultrafiltration membranes can be used for wastewater treatment and resource recovery. With the increasing demand for high-efficiency separation technology in the fields of biopharmaceuticals, food and beverages, and environmental protection, MWCO5000 ultrafiltration membranes have occupied an important position in modern separation technology.
[0003] By developing high-performance MWCO 5000 ultrafiltration membranes, we can not only improve separation efficiency, but also promote the development of membrane separation technology and promote technological progress and innovation in related industries. Therefore, the research and development of MWCO 5000 ultrafiltration membranes has important scientific research value. The research and development of MWCO 5000 ultrafiltration membranes not only needs to consider the selection of materials, but also needs to optimize the preparation process and performance to ensure its excellent performance in practical applications.
[0004] The traditional preparation method of ultrafiltration membrane is usually the phase inversion method, which forms a membrane by exchanging solvent and non-solvent, and can accurately control the pore size distribution of the membrane. However, the ultrafiltration membranes that can achieve MWCO 5000 separation performance on the market are basically composite ultrafiltration membranes, that is, it is necessary to synthesize a composite layer on the ultrafiltration membrane prepared by the phase inversion method, and there are almost no ultrafiltration membranes that can directly prepare MWCO 5000 separation performance by the phase inversion method. Therefore, the current preparation method of MWCO 5000 ultrafiltration membrane has the technical problem of complicated process. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for preparing an ultrafiltration membrane and an ultrafiltration membrane, so as to solve the technical problem that the preparation method of the MWCO 5000 ultrafiltration membrane in the prior art has complicated process.
[0006] In order to achieve the above object, the present invention first provides a method for preparing an ultrafiltration membrane, and the technical scheme is as follows:
[0007] The method for preparing an ultrafiltration membrane comprises the following steps:
[0008] (1) preparing a precursor solution including an organic solvent, polyethersulfone, sulfonated polysulfone and a porogen;
[0009] (2) performing vacuum degassing on the precursor solution to obtain a film casting solution;
[0010] (3) The casting solution is loaded onto a carrier and then subjected to a gel bath treatment to obtain an ultrafiltration membrane.
[0011] As a further improvement to the above-mentioned method for preparing the ultrafiltration membrane: in step (1), the precursor solution also includes a plasticizer and an inorganic salt.
[0012] As a further improvement of the above-mentioned method for preparing the ultrafiltration membrane: the organic solvent includes N,N-dimethylacetamide; the porogen includes polyvinyl pyrrolidone-K30 and / or polyethylene glycol 600; the plasticizer includes diethylene glycol; and the inorganic salt includes lithium chloride.
[0013] As a further improvement of the above-mentioned method for preparing the ultrafiltration membrane: in step (1), the precursor solution contains, by weight, 55 to 65 parts of N,N-dimethylacetamide, 15 to 30 parts of polyethersulfone, 1 to 18 parts of sulfonated polysulfone, 0.5 to 15 parts of polyvinylpyrrolidone-K30, 0.2 to 5 parts of polyethylene glycol 600, 0.5 to 11 parts of diethylene glycol and 0.2 to 5 parts of lithium chloride.
[0014] As a further improvement of the above-mentioned method for preparing the ultrafiltration membrane: in step (1), in step (1), the weight ratio of polyethersulfone to sulfonated polysulfone in the precursor solution is 1:1.
[0015] As a further improvement of the above-mentioned method for preparing the ultrafiltration membrane: in step (1), polyethersulfone and sulfonated polysulfone are added to a mixed solution consisting of an organic solvent, a porogen, a plasticizer and an inorganic salt under heating and stirring conditions, and after the addition is completed, the mixture is stirred for a period of time to obtain a precursor solution.
[0016] As a further improvement of the above-mentioned method for preparing the ultrafiltration membrane: in step (1), when the temperature of the mixed solution reaches 50-80°C, polyethersulfone and sulfonated polysulfone are added, and after the addition is completed, stirring is continued for 12-24 hours to obtain a precursor solution.
[0017] As a further improvement of the above-mentioned method for preparing the ultrafiltration membrane: in step (2), the precursor solution is vacuum degassed at 50° C. for 6 to 12 hours to obtain a casting solution.
[0018] As a further improvement of the above-mentioned method for preparing the ultrafiltration membrane: in step (3), a non-woven fabric is used as a carrier, a casting liquid at a temperature of 30 to 60°C is loaded onto the non-woven fabric, and a gel bath treatment is performed in pure water for 2 to 150 minutes to obtain an ultrafiltration membrane.
[0019] In order to achieve the above object, the present invention secondly provides an ultrafiltration membrane, and the technical solution is as follows:
[0020] The ultrafiltration membrane is prepared by the preparation method of the ultrafiltration membrane described in the first aspect above.
[0021] The preparation method of the ultrafiltration membrane and the ultrafiltration membrane of the present invention have the following advantages:
[0022] First, compared with the traditional polysulfone substrate, the polyethersulfone substrate introduced in the present invention has the following advantages: (1) Higher heat resistance: The glass transition temperature (Tg) of polyethersulfone is about 220°C, which is higher than the Tg of polysulfone (about 190°C), which means that polyethersulfone can maintain better mechanical strength and stability at high temperatures and is suitable for the preparation of ultrafiltration membranes that require higher heat resistance. (2) Better chemical stability: Polyethersulfone exhibits better chemical stability in acids, alkalis, oxidants and most organic solvents, which makes it more corrosion-resistant and durable in various chemical environments and more reliable when handling corrosive or chemically complex liquids. (3) Higher antioxidant performance: The molecular structure of polyethersulfone contains ether bonds (-O-), which gives it strong antioxidant properties and can reduce the performance degradation of the membrane caused by oxidation during long-term use. (4) Better mechanical strength: Polyethersulfone has higher mechanical strength and toughness, can withstand greater pressure and mechanical stress, and is not easy to break or deform, which is particularly important for the use of ultrafiltration membranes in high-pressure filtration and separation processes. (5) Better hydrophilicity: The hydrophilicity of polyethersulfone is better than that of polysulfone, which makes it easier for polyethersulfone to form a uniform pore structure during the membrane preparation process, which helps to improve the flux and anti-pollution ability of the membrane and reduce the accumulation of pollutants on the membrane surface. (6) Higher biocompatibility: Polyethersulfone has good biocompatibility and is often used in the production of medical devices and biological products. It can reduce bacterial attachment and membrane biofouling during water treatment.
[0023] Second, on the basis of polyethersulfone, the present invention further introduces sulfonated polysulfone, which has the following advantages: (1) Improved hydrophilicity: Sulfonated polysulfone molecules contain sulfonic acid groups (-SO3H), which are strong hydrophilic groups that can significantly improve the hydrophilicity of the membrane, making the membrane easier to wet in water, and improving the water flux and separation efficiency of the membrane; enhanced hydrophilicity can reduce the hydrophobic interaction between the membrane surface and pollutants, reduce the adsorption of pollutants such as proteins and oils on the membrane surface, thereby reducing the pollution tendency of the membrane and extending the service life of the membrane. (2) Increased charge: The sulfonic acid group of sulfonated polysulfone carries a negative charge, so that the membrane has a certain charge in the aqueous solution, which helps to exclude pollutants and solute molecules with the same charge through electrostatic repulsion, thereby improving the selectivity and interception performance of the membrane. (3) Enhanced mechanical properties: Sulfonated polysulfone still retains the good mechanical properties of polysulfone materials, including high strength and toughness, and can form a composite structure with other polymers to give the membrane good mechanical stability, making it less likely to break or deform during operation. (4) Improving separation performance: The introduction of sulfonic acid groups helps to adjust the pore size and pore structure of the membrane, making the pore size distribution of the membrane more uniform, which helps to improve the separation accuracy of the membrane.
[0024] Third, the sulfonic acid group of the sulfonated polysulfone easily forms hydrogen bonds with the porogen in an organic solvent, and this interaction can increase the entanglement between polymer chains and promote the formation of a three-dimensional network structure inside the membrane, thereby further reducing the pores of the membrane while increasing the viscosity of the casting solution, reducing the molecular weight cutoff of the membrane, and optimizing the structural stability and filtration performance of the membrane. Thus, the present invention can directly obtain an ultrafiltration membrane with a separation performance of MWCO 5000 through a phase inversion step through the interaction between the sulfonic acid group of the sulfonated polysulfone and the porogen, without further synthesizing a composite layer, significantly reducing the process, and saving manufacturing time and cost.
[0025] In summary, the preparation method of the ultrafiltration membrane of the present invention has a simple process and low material cost. The obtained ultrafiltration membrane has higher and more stable separation performance, which effectively solves the technical problem of the complicated process of the preparation method of MWCO 5000 ultrafiltration membrane in the prior art, has a wide range of applications and strong practicality.
[0026] The present invention is further described below by way of specific embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be learned through practice of the present invention. DETAILED DESCRIPTION
[0027] The present invention is described clearly and completely below. A person skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention, it should be noted that:
[0028] The technical solutions and technical features provided in each part of the present invention, including the following description, may be combined with each other if there is no conflict.
[0029] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0030] About the terms and units in the present invention: The terms "include", "have" and any variations thereof in the description and claims of the present invention and related parts are intended to cover non-exclusive inclusions.
[0031] Example 1
[0032] The preparation method of the ultrafiltration membrane of this embodiment comprises the following steps:
[0033] (1) Add N,N-dimethylacetamide and a porogen, wherein the porogen is polyethylene glycol 600, into a three-necked flask, place the three-necked flask in an electric heating mantle for heating and stirring, add polyethersulfone and sulfonated polysulfone to the mixed solution when the temperature reaches 60° C., stir for 12 hours after the addition is completed, and obtain a precursor solution; wherein the precursor solution contains 60.4 parts of N,N-dimethylacetamide, 2 parts of polyethylene glycol 600, 16.8 parts of polyethersulfone and 16.8 parts of sulfonated polysulfone by weight.
[0034] (3) The precursor solution was vacuum degassed at 50°C for 9 hours to obtain a casting solution.
[0035] (4) Using a scraper with a blade spacing of 150 μm and a moving speed of 10 m / min, a casting solution at a temperature of 50°C is loaded onto the non-woven fabric, and then a gel bath treatment is performed in pure water for 10 minutes to allow N,N-dimethylacetamide and pure water to exchange and solidify into a membrane, thereby obtaining an ultrafiltration membrane.
[0036] The test results show that the flux of the ultrafiltration membrane is 41.7L / (m 2 h), the retention rate of polyethylene glycol 5000 is 94.57%, and the retention rate of polyethylene glycol 3500 is 80.23%.
[0037] Example 2
[0038] (1) Add N,N-dimethylacetamide, a porogen and a plasticizer into a three-necked flask, wherein the porogen is polyethylene glycol 600 and the plasticizer is diethylene glycol. Place the three-necked flask in an electric heating mantle for heating and stirring. When the temperature reaches 60° C., add polyethersulfone and sulfonated polysulfone to the mixed solution. After the addition is completed, stir for 12 hours to obtain a precursor solution. The precursor solution contains 60.4 parts of N,N-dimethylacetamide, 2 parts of polyethylene glycol 600, 4 parts of diethylene glycol, 16.8 parts of polyethersulfone and 16.8 parts of sulfonated polysulfone by weight.
[0039] (3) The precursor solution was vacuum degassed at 50°C for 9 hours to obtain a casting solution.
[0040] (4) Using a scraper with a blade spacing of 150 μm and a moving speed of 10 m / min, a casting solution at a temperature of 50°C is loaded onto the non-woven fabric, and then a gel bath treatment is performed in pure water for 10 minutes to allow N,N-dimethylacetamide and pure water to exchange and solidify into a membrane, thereby obtaining an ultrafiltration membrane.
[0041] The test results show that the flux of the ultrafiltration membrane is 41.3L / (m 2 h), the retention rate of polyethylene glycol 5000 was 95.34%, and the retention rate of polyethylene glycol 3500 was 81.47%.
[0042] Example 3
[0043] (1) Add N,N-dimethylacetamide, a porogen, a plasticizer and an inorganic salt into a three-necked flask, wherein the porogen is polyethylene glycol 600, the plasticizer is diethylene glycol, and the inorganic salt is lithium chloride. Place the three-necked flask in an electric heating mantle for heating and stirring. When the temperature reaches 60° C., add polyethersulfone and sulfonated polysulfone to the mixed solution. After the addition is completed, stir for 12 hours to obtain a precursor solution; wherein the precursor solution contains 60.4 parts of N,N-dimethylacetamide, 2 parts of polyethylene glycol 600, 4 parts of diethylene glycol, 2 parts of lithium chloride, 16.8 parts of polyethersulfone and 16.8 parts of sulfonated polysulfone by weight.
[0044] (3) The precursor solution was vacuum degassed at 50°C for 9 hours to obtain a casting solution.
[0045] (4) Using a scraper with a blade spacing of 150 μm and a moving speed of 10 m / min, a casting solution at a temperature of 50°C is loaded onto the non-woven fabric, and then a gel bath treatment is performed in pure water for 10 minutes to allow N,N-dimethylacetamide and pure water to exchange and solidify into a membrane, thereby obtaining an ultrafiltration membrane.
[0046] The test results show that the flux of the ultrafiltration membrane is 39.5L / (m 2h), the retention rate of polyethylene glycol 5000 is 95.89%, and the retention rate of polyethylene glycol 3500 is 81.85%.
[0047] Example 4
[0048] (1) Add N,N-dimethylacetamide, a porogen, a plasticizer and an inorganic salt into a three-necked flask, wherein the porogen is polyethylene glycol 600 and polyvinyl pyrrolidone-K30, the plasticizer is diethylene glycol, and the inorganic salt is lithium chloride. Place the three-necked flask in an electric heating mantle for heating and stirring. When the temperature reaches 60° C., add polyether sulfone and sulfonated polysulfone to the mixed solution. After the addition is completed, stir for 12 hours to obtain a precursor solution; wherein the precursor solution contains, by weight, 60.4 parts of N,N-dimethylacetamide, 1.5 parts of polyethylene glycol 600, 4.8 parts of polyvinyl pyrrolidone-K30, 4 parts of diethylene glycol, 2 parts of lithium chloride, 16.8 parts of polyether sulfone and 16.8 parts of sulfonated polysulfone.
[0049] (3) The precursor solution was vacuum degassed at 50°C for 9 hours to obtain a casting solution.
[0050] (4) Using a scraper with a blade spacing of 150 μm and a moving speed of 10 m / min, a casting solution at a temperature of 50°C is loaded onto the non-woven fabric, and then a gel bath treatment is performed in pure water for 10 minutes to allow N,N-dimethylacetamide and pure water to exchange and solidify into a membrane, thereby obtaining an ultrafiltration membrane.
[0051] The test results show that the flux of the ultrafiltration membrane is 34.6L / (m 2 h), the retention rate of polyethylene glycol 5000 was 96.24%, and the retention rate of polyethylene glycol 3500 was 82.41%.
[0052] Example 5
[0053] (1) Add N,N-dimethylacetamide, a porogen, a plasticizer and an inorganic salt into a three-necked flask, wherein the porogen is polyethylene glycol 600 and polyvinyl pyrrolidone-K30, the plasticizer is diethylene glycol, and the inorganic salt is lithium chloride. Place the three-necked flask in an electric heating mantle for heating and stirring. When the temperature reaches 60° C., add polyether sulfone and sulfonated polysulfone to the mixed solution. After the addition is completed, stir for 12 hours to obtain a precursor solution; wherein the precursor solution contains, by weight, 55 parts of N,N-dimethylacetamide, 0.2 parts of polyethylene glycol 600, 0.5 parts of polyvinyl pyrrolidone-K30, 0.5 parts of diethylene glycol, 0.2 parts of lithium chloride, 15 parts of polyether sulfone and 15 parts of sulfonated polysulfone.
[0054] (3) The precursor solution was vacuum degassed at 50°C for 9 hours to obtain a casting solution.
[0055] (4) Using a scraper with a blade spacing of 150 μm and a moving speed of 10 m / min, a casting solution at a temperature of 50°C is loaded onto the non-woven fabric, and then a gel bath treatment is performed in pure water for 10 minutes to allow N,N-dimethylacetamide and pure water to exchange and solidify into a membrane, thereby obtaining an ultrafiltration membrane.
[0056] The test results show that the flux of the ultrafiltration membrane is 46.7L / (m 2 h), the retention rate of polyethylene glycol 5000 is 93.32%, and the retention rate of polyethylene glycol 3500 is 78.46%.
[0057] Example 6
[0058] (1) Add N,N-dimethylacetamide, a porogen, a plasticizer and an inorganic salt into a three-necked flask, wherein the porogen is polyethylene glycol 600, the plasticizer is diethylene glycol, and the inorganic salt is lithium chloride. Place the three-necked flask in an electric heating mantle for heating and stirring. When the temperature reaches 60° C., add polyethersulfone and sulfonated polysulfone to the mixed solution. After the addition is completed, stir for 12 hours to obtain a precursor solution; wherein the precursor solution contains, by weight, 57.1 parts of N,N-dimethylacetamide, 1 part of polyethylene glycol 600, 9.8 parts of diethylene glycol, 1 part of lithium chloride, 21.4 parts of polyethersulfone and 9.2 parts of sulfonated polysulfone.
[0059] (3) The precursor solution was vacuum degassed at 50°C for 9 hours to obtain a casting solution.
[0060] (4) Using a scraper with a blade spacing of 150 μm and a moving speed of 10 m / min, a casting solution at a temperature of 50°C is loaded onto the non-woven fabric, and then a gel bath treatment is performed in pure water for 10 minutes to allow N,N-dimethylacetamide and pure water to exchange and solidify into a membrane, thereby obtaining an ultrafiltration membrane.
[0061] The test results show that the flux of the ultrafiltration membrane is 54.7L / (m 2 h), the retention rate of polyethylene glycol 5000 is 92.58%, and the retention rate of polyethylene glycol 3500 is 77.16%.
[0062] Example 7
[0063] (1) Add N,N-dimethylacetamide, a porogen and a plasticizer into a three-necked flask, wherein the porogen is polyvinyl pyrrolidone-K30, the plasticizer is diethylene glycol, and the inorganic salt is lithium chloride. Place the three-necked flask in an electric heating mantle for heating and stirring. When the temperature reaches 60° C., add polyether sulfone and sulfonated polysulfone to the mixed solution. After the addition is completed, stir for 12 hours to obtain a precursor solution; wherein the precursor solution contains 58.3 parts of N,N-dimethylacetamide, 11.8 parts of polyvinyl pyrrolidone-K30, 5.8 parts of diethylene glycol, 16.5 parts of polyether sulfone and 16.5 parts of sulfonated polysulfone by weight.
[0064] (3) The precursor solution was vacuum degassed at 50°C for 9 hours to obtain a casting solution.
[0065] (4) Using a scraper with a blade spacing of 150 μm and a moving speed of 10 m / min, a casting solution at a temperature of 50°C is loaded onto the non-woven fabric, and then a gel bath treatment is performed in pure water for 10 minutes to allow N,N-dimethylacetamide and pure water to exchange and solidify into a membrane, thereby obtaining an ultrafiltration membrane.
[0066] The test results show that the flux of the ultrafiltration membrane is 50.8L / (m 2 h), the retention rate of polyethylene glycol 5000 is 93.14%, and the retention rate of polyethylene glycol 3500 is 77.87%.
[0067] Example 8
[0068] (1) Add N,N-dimethylacetamide, a porogen and an inorganic salt into a three-necked flask, wherein the porogen is polyethylene glycol 600 and polyvinyl pyrrolidone-K30, the plasticizer is diethylene glycol, and the inorganic salt is lithium chloride. Place the three-necked flask in an electric heating mantle for heating and stirring. When the temperature reaches 60° C., add polyether sulfone and sulfonated polysulfone to the mixed solution. After the addition is completed, stir for 12 hours to obtain a precursor solution; wherein the precursor solution contains, by weight, 59.8 parts of N,N-dimethylacetamide, 3 parts of polyethylene glycol 600, 7.5 parts of polyvinyl pyrrolidone-K30, 3 parts of lithium chloride, 30 parts of polyether sulfone and 1 part of sulfonated polysulfone.
[0069] (3) The precursor solution was vacuum degassed at 50°C for 9 hours to obtain a casting solution.
[0070] (4) Using a scraper with a blade spacing of 150 μm and a moving speed of 10 m / min, a casting solution at a temperature of 50°C is loaded onto the non-woven fabric, and then a gel bath treatment is performed in pure water for 10 minutes to allow N,N-dimethylacetamide and pure water to exchange and solidify into a membrane, thereby obtaining an ultrafiltration membrane.
[0071] The test results show that the flux of the ultrafiltration membrane is 58.4L / (m 2h), the retention rate of polyethylene glycol 5000 is 91.66%, and the retention rate of polyethylene glycol 3500 is 75.93%.
[0072] Example 9
[0073] (1) Add N,N-dimethylacetamide, a porogen, a plasticizer and an inorganic salt into a three-necked flask, wherein the porogen is polyethylene glycol 600 and polyvinyl pyrrolidone-K30, the plasticizer is diethylene glycol, and the inorganic salt is lithium chloride. Place the three-necked flask in an electric heating mantle for heating and stirring. When the temperature reaches 60° C., add polyether sulfone and sulfonated polysulfone to the mixed solution. After the addition is completed, stir for 12 hours to obtain a precursor solution; wherein the precursor solution contains, by weight, 65 parts of N,N-dimethylacetamide, 5 parts of polyethylene glycol 600, 15 parts of polyvinyl pyrrolidone-K30, 11 parts of diethylene glycol, 5 parts of lithium chloride, 18 parts of polyether sulfone and 18 parts of sulfonated polysulfone.
[0074] (3) The precursor solution was vacuum degassed at 50°C for 9 hours to obtain a casting solution.
[0075] (4) Using a scraper with a blade spacing of 150 μm and a moving speed of 10 m / min, a casting solution at a temperature of 50°C is loaded onto the non-woven fabric, and then a gel bath treatment is performed in pure water for 10 minutes to allow N,N-dimethylacetamide and pure water to exchange and solidify into a membrane, thereby obtaining an ultrafiltration membrane.
[0076] The test results show that the flux of the ultrafiltration membrane is 45.6L / (m 2 h), the retention rate of polyethylene glycol 5000 is 93.52%, and the retention rate of polyethylene glycol 3500 is 79.55%.
[0077] Comparative Example 1
[0078] Compared with Example 8, the ultrafiltration membrane of this example is different in that it does not contain sulfonated polysulfone.
[0079] The test results show that the flux of the ultrafiltration membrane is 62.6L / (m 2 h), the retention rate of polyethylene glycol 5000 is 87.55%, and the retention rate of polyethylene glycol 3500 is 71.24%.
[0080] The flux (pure water) and retention performance of the ultrafiltration membranes in the above examples and control examples were tested according to the "Ultrafiltration Membrane Test Method" (GB / T 32360-2015), as follows:
[0081] 1. Take several (not less than 4) samples. The samples should be free of obvious defects such as wrinkles and damages. The size of the samples should meet the requirements of the sealing ring that completely covers the evaluation pool. The effective membrane area of the samples in the evaluation pool should not be less than 2.5×10-3 m 2 ; Prepare polyethylene glycol 5000 solution and polyethylene glycol 3500 solution with a concentration of 1000 mg / L.
[0082] 2. Soak the sample in deionized water or distilled water for 30 minutes;
[0083] 3. Retention performance test: Load the sample into the evaluation tank, start the booster pump, and adjust the operating pressure to 120psi; after stable operation at constant pressure for 30 minutes, use a measuring cylinder to collect a certain amount of stock solution (polyethylene glycol 5000 solution or polyethylene glycol 3500 solution, a single sample is not less than 30 ml) The permeate produced after passing through the sample, use a stopwatch to calculate the required time, and use the wet chemical oxidation method to determine the total organic carbon (TOC) of the stock solution and the permeate.
[0084] Flux test: Take another sample and put it into the evaluation tank, turn on the water supply pump, adjust the operating pressure to 120psi for cross-flow filtration, and reduce the pressure to 80psi after stable operation at constant pressure for 30 minutes. Dead-end filter for 10 minutes. When the temperature stabilizes at 25℃±0.5℃, use a measuring cup to collect the water produced after passing through the sample, and use a stopwatch to calculate the time required.
[0085] 4. After the test is completed, slowly reduce the operating pressure to below 0.05MPa and turn off the booster pump or water supply pump.
[0086] The flux was calculated using the following formula:
[0087]
[0088] Where J is the flux, the unit is L / (m 2 ﹒ h); V is the sampling volume of the measuring cylinder, in L; T is the sampling time, in h; A is the effective area of the sample, in m 2 .
[0089] The retention performance was calculated using the following formula:
[0090]
[0091] Where, R is the interception rate, in %; C P is the TOC of the permeate, in mg / L; C f is the TOC of the original solution, in mg / L.
[0092] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without making any creative work shall fall within the scope of protection of the present invention.
Claims
1. A method for preparing an ultrafiltration membrane, characterized in that: The following steps are involved: (1) preparing a precursor solution including an organic solvent, polyethersulfone, sulfonated polysulfone and a porogen; (2) performing vacuum degassing on the precursor solution to obtain a film casting solution; (3) The casting solution is loaded onto a carrier and then subjected to a gel bath treatment to obtain an ultrafiltration membrane.
2. The method for preparing an ultrafiltration membrane according to claim 1, characterized in that: In step (1), the precursor solution also includes a plasticizer and an inorganic salt.
3. The method for preparing an ultrafiltration membrane according to claim 2, characterized in that: The organic solvent includes N,N-dimethylacetamide; the porogen includes polyvinyl pyrrolidone-K30 and / or polyethylene glycol 600; the plasticizer includes diethylene glycol; and the inorganic salt includes lithium chloride.
4. The method for preparing an ultrafiltration membrane according to claim 3, characterized in that: In step (1), the precursor solution contains, by weight, 55 to 65 parts of N,N-dimethylacetamide, 15 to 30 parts of polyethersulfone, 1 to 18 parts of sulfonated polysulfone, 0.5 to 15 parts of polyvinylpyrrolidone-K30, 0.2 to 5 parts of polyethylene glycol 600, 0.5 to 11 parts of diethylene glycol and 0.2 to 5 parts of lithium chloride.
5. The method for preparing an ultrafiltration membrane according to claim 4, characterized in that: In step (1), the weight ratio of polyethersulfone to sulfonated polysulfone in the precursor solution is 1:
1.
6. The method for preparing an ultrafiltration membrane according to claim 2, characterized in that: In step (1), polyethersulfone and sulfonated polysulfone are added to a mixed solution consisting of an organic solvent, a porogen, a plasticizer and an inorganic salt under heating and stirring. After the addition is completed, the mixture is stirred for a period of time to obtain a precursor solution.
7. The method for preparing an ultrafiltration membrane according to claim 6, characterized in that: In step (1), when the temperature of the mixed solution reaches 50-80° C., polyethersulfone and sulfonated polysulfone are added, and stirring is continued for 12-24 hours after the addition is completed to obtain a precursor solution.
8. The method for preparing an ultrafiltration membrane according to claim 1, characterized in that: In step (2), the precursor solution is vacuum degassed at 50° C. for 6 to 12 hours to obtain a casting solution.
9. The method for preparing an ultrafiltration membrane according to claim 1, characterized in that: In step (3), a non-woven fabric is used as a carrier, a casting solution at a temperature of 30 to 60° C. is loaded onto the non-woven fabric, and a gel bath treatment is performed in pure water for 2 to 150 minutes to obtain an ultrafiltration membrane.
10. Ultrafiltration membrane, characterized in that: The ultrafiltration membrane is prepared by the preparation method of the ultrafiltration membrane according to any one of claims 1 to 9.